2019
DOI: 10.4236/aim.2019.93014
|View full text |Cite
|
Sign up to set email alerts
|

Folate Enrichment of <i>Ogi</i> (a Fermented Cereal Gruel) Using Folate Producing Starter Cultures

Abstract: This study was aimed at selecting starter cultures for bio-enriching ogi (fermented cereal gruel) using folate-producing microorganisms. The folate-producing microorganisms were isolated by incorporating folate analogue, methotrexate in the isolation medium and further screened for folate production by growth in Folic Acid Casei Medium. Folate production was quantified using 3-aminophenol spectrophotometric method. Folate-producing lactic acid bacteria from fermenting maize slurry were species of Lactobacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Our study has also revealed the possibility of increasing folate by fermentation as more than 100 % folate retention was observed in barley fermentation. This result suggests that folate producing microorganisms may dominate those that do not produce or consume folate as previous studies confirmed the co-occurrence of both folate producing and consuming microorganisms during fermentation process (Okoroafor et al ., 2019). The type of microorganisms and the overall conditions that led to folate production in barley fermentation needs further detail examination.…”
Section: Discussionsupporting
confidence: 72%
“…Our study has also revealed the possibility of increasing folate by fermentation as more than 100 % folate retention was observed in barley fermentation. This result suggests that folate producing microorganisms may dominate those that do not produce or consume folate as previous studies confirmed the co-occurrence of both folate producing and consuming microorganisms during fermentation process (Okoroafor et al ., 2019). The type of microorganisms and the overall conditions that led to folate production in barley fermentation needs further detail examination.…”
Section: Discussionsupporting
confidence: 72%
“…Dominant L. brevis activity in the fermenting mash enhanced by the presence of S. cerevisiae when they were both used as starter cultures for ogi may be responsible for the stable nal pH and high acid production during starter culture fermentation (Table2) (EgwimEvans et al, 2013). This indicate a better product shelf life since organic acids produced by lactic acid bacteria has inhibitory effect against many spoilage and pathogenic organisms(Agriopoulou et al, 2020).Lysine and methionine producing capabilities of the starter cultures used conform to the results ofTeniola and Odunfa (2001) andOkoroafor et al (2019) on the possibility of improving food nutrients by microbial fermentation with nutrient hyperproducing microorganisms. The result con rm the presence of lysine and methionine producing Lactobacillus and yeast as well as their potential for ogi nutritional improvement(Odunfa et al, 2001) Chung and Fields (1986).…”
supporting
confidence: 54%
“…The wetmilled mash was further fermented for 48 h. The traditionally prepared reference control from whole maize grains was wetsieved before further fermentation. After fermentation, the pH and percentage total titratable acidity of the fermented mash samples were measured (Okoroafor et al, 2019). Lactobacillus brevis XO43 and Saccharomyces cerevisiae OY4 used as starter cultures were isolated and con rmed with the stock cultures using various morphological and biochemical tests.…”
Section: Fermentation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the vitamin content, fermentation with sourdough can be applied. Certain strains of LAB can synthesise vitamins such as riboflavin, thiamine, and folate [17,24,[95][96][97]. Mihhalevski et al (2013) [60] also showed that the content of nicotinamide increased during processing by tenfold, presumably due to microbial activity during sourdough fermentation.…”
Section: Sourdough Fermentation and Vitaminsmentioning
confidence: 99%